Edukasi Pencegahan Stunting pada Balita di Posyandu Wilayah Kerja Puskesmas Kandai Kota Kendari - Renni Meliahsari; Akifah Akifah; Suci Adilla Ainiya; Tri Qhofifah Indaryani; Vanny Septiani (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Stunting remains a chronic nutritional problem in Indonesia that affects children’s physical growth and development. Limited community knowledge regarding balanced nutrition and appropriate feeding practices contributes significantly to stunting prevalence. This community service activity aimed to improve knowledge and awareness of stunting prevention among mothers and the community through nutrition education. The method employed an interactive and participatory educational approach, including counseling sessions, discussions, question-and-answer activities, and leaflet distribution. The program was conducted in Kandai Village involving mothers of toddlers and posyandu cadres. The results indicated an improvement in participants’ understanding of stunting definition, risk factors, long-term impacts, the importance of nutrition during the first 1,000 days of life, exclusive breastfeeding, and appropriate complementary feeding practices. This educational intervention encouraged greater awareness of regular growth monitoring and the application of balanced nutrition in daily life to prevent stunting.